2014
DOI: 10.1248/bpb.b13-00613
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Fur Binding to the Oxidative Stress Response Gene Promoter in the Facultative Anaerobic Archaeon <i>Thermoplasma volcanium</i>

Abstract: The genome of the facultative anaerobic thermoacidophilic archaeon Thermoplasma volcanium contains the open-reading frames (ORFs) tvsod and tvogg, which are predicted to encode a putative superoxide dismutase and an 8-oxoguanine DNA glycosylase, respectively. Tvsod is immediately upstream of tvogg, and these two ORFs are aligned in a head-to-tail manner in a single operon. A previous study showed that T. volcanium contains an ORF (TVN0292) encoding the ferric uptake regulator (Fur) and that the T. volcanium Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Under excessive iron, however, Fur also plays a role in the positive regulation of genes encoding iron-utilizing enzymes (e.g., SodB, SOD) and iron storage proteins ( Latifi et al, 2009 ). Minoshima et al (2014) demonstrated the role of Fur in enhancing resistance to ROSs by Thermoplasma volcanium, a facultative archaeon. Thus Fur encoded by an ORF (TVN0292) [T .…”
Section: Crosstalk Between Oxidative and Other Stressesmentioning
confidence: 98%
See 1 more Smart Citation
“…Under excessive iron, however, Fur also plays a role in the positive regulation of genes encoding iron-utilizing enzymes (e.g., SodB, SOD) and iron storage proteins ( Latifi et al, 2009 ). Minoshima et al (2014) demonstrated the role of Fur in enhancing resistance to ROSs by Thermoplasma volcanium, a facultative archaeon. Thus Fur encoded by an ORF (TVN0292) [T .…”
Section: Crosstalk Between Oxidative and Other Stressesmentioning
confidence: 98%
“…Thus Fur encoded by an ORF (TVN0292) [T . volcanium Fur protein (TvFur)] resists excessive iron accumulation ( Minoshima et al, 2014 ).…”
Section: Crosstalk Between Oxidative and Other Stressesmentioning
confidence: 99%
“…In the process of genomic SELEX experiments using a ferric uptake regulatory protein, TvFur, we found that TvFur binds the promoter region of TVG_RS00310 ( TVN0061 ), which encodes superoxide dismutase, TvSOD [ 18 ]. The TvSOD gene is located at the 5′ end of an operon.…”
Section: Introductionmentioning
confidence: 99%